Behavior of the Superstition Hills fault during the past 330 years - Sieh, Kerry (2013)
We have investigated the recent prehistoric behavior of the Superstition Hills fault by examining its effect on the beach deposits of ancient Lake Cahuilla. Excavation of these sediments in three dimensions where they are cut by the fault has enabled determination of total offset since the latest highstand of the lake, about 330 years ago. As of 3 March 1988, total dextral offset was 1106 ± 50 mm. About 609 mm of this amount can be attributed to one or more slip events before 1987. The remaining slip occurred during the moderate earthquake of 24 November 1987 and as subsequent aftercreep. Additional aftercreep here might produce a total of 1210 ± 100 mm for that event. Thus, if afterslip continues according to our prediction, slip associated with the penultimate seismic slip event on the Superstition Hills fault was only about half of the co-seismic slip and predicted afterslip associated with the 1987 earthquake. This difference, established at a single site on the fault, may reflect a larger size for the 1987 event than for its predecessor. We calculate that the slip rate of the Superstition Hills fault zone, averaged over the past 330 years, is between about 2 and at least 6 mm/yr at this site. During this time, the average interval between large surface slip events on the Superstition Hills fault has been between about 150 and 300 years. The pre-1987 slip event documented in our excavations could have occurred at any time between A.D. 1660 and about A.D. 1915. These results are significant for understanding earthquake recurrence and patterns of earthquakes in the Imperial and Coachella Valleys.